From Traditionality to Modernity: How the Ma’had Aly Contributes to Muslim Society in Indonesia - Taufiq, Firmanda (Muslim Education Review, 2024)
Ma’had Aly is one of the religious-educational institutions based in Islamic boarding schools. This institution is an important actor in the transmission of intellectual and Islamic religious knowledge. In this context, students in Islamic boarding schools study the kitab kuning (yellow book) or kitab turath (traditional Islamic books) and try to contextualize them with the times. Moreover, the problems of the times are increasingly complex, so ma’had aly tries to answer these challenges. This article seeks to examine how ma’had aly has become an important actor in the context of the circulation and transmission of Islamic religious knowledge in Indonesia. This research focuses on three ma’had aly in Indonesia; namely, Ma’had Aly Pondok Pesantren Al-Munawwir Krapyak, Ma’had Aly Pondok Pesantren Al-Falah Ploso, and Ma’had Aly Pondok Pesantren Salafiyah Syafi'iyah Situbondo. The findings in this study show that ma’had aly has contributed greatly to the landscape of the map of intellectual transmission and Islamic religious knowledge in Indonesia. Not only that, ma’had aly also has its style in the pattern of teaching and education, especially related to contextualization between text and context in a heterogeneous society with the complexity of the problems faced. In addition, from initially focusing only on traditional knowledge, now ma’had aly is transforming towards modernity by combining text and context, where the problems of society are increasingly complex.